A 2D PSA On Essential Oils Usage And Its Effects On Children’s Hormonal Growth: 2D PSA on essential oil effects on children’s hormon and how to use them responsibly - Nur Dini Jamaludin; Jessifa Joanna Mohd Supian (Journal of Computing Technologies and Creative Content, 2022)
Essential oils are concentrated extracts of plants, specifically their flowers, leaves, and fruits. These extracts are usually made through the process of distillation or cold pressing. In fact, "essential" means that the oil is a key to the character of the plant itself. They can be used for aromatherapy and cosmetic purposes, among other things. They also have a strong odour, which is why they are utilised in food flavourings and perfumery. For many people, specifically in Malaysia, the idea of using essential oils is a new concept. The essential oil industry appears to be thriving as a result of self-care and pampering practices, as sales of candles, aromatherapy, and detox products have increased significantly since the COVID-19 pandemic. The study of essential oils' health impacts is still ongoing, and it is still too early to know how they function and what their long-term implications might be. However, according to a new study published in 2018, the components in lavender and tea tree oils can disrupt the hormonal system in children. As a result, the aim of this research is to produce a 2D animated video PSA based on the ADDIE model framework that explains the impact of Lavender and Tea tree Oils on children's hormonal growth. This study also aims to raise awareness among Malaysian parents about the impact on their children's endocrine systems.